Correction to: Utilization of non-edible bio-feedstock Pongamia Pinnata-diethyl ether ternary fuel blend supplemented with graphene oxide nanoparticles on CRDi engine characteristics (Journal of Thermal Analysis and Calorimetry, (2024), 149, 11, (5687-5712), 10.1007/s10973-024-13143-2) - Soudagar M.E.M.; Kiong T.S.; Ramesh S.; Ghazali N.N.N.; Kalam M.A.; Mujtaba M.A.; Venu H.; Nur-E-Alam M.; Ali H.M. (Springer Science and Business Media B.V., 2025)
In this article the affiliation details for first author, Manzoore Elahi M. Soudagar were incorrectly given as 'Department of Mechanical Engineering, Faculty of Engineering, University Malaya, 50603, Kuala Lumpur, Malaysia and Centre of Molecular Medicine and Diagnostics (COMManD), Saveetha Dental College and Hospital, Saveetha Institute of Medical and Technical Sciences, Saveetha University, 600077, Chennai, India'. The corrected affiliation should have been 'Faculty of Engineering, Lishui University, 323000 Lishui, Zhejiang, People's Republic of China? which was missing in the original version. The affiliation details for the author Mohammad Nur-E-Alam were incorrectly given as 'Division of Research and Development, Lovely Professional University, Phagwara, Punjab 144411, Australia' but should have been as 'Division of Research and Development, Lovely Professional University, Phagwara, Punjab 144411, India'. The original article has been corrected. ? Akadmiai Kiad, Budapest, Hungary 2024.